Strategi Peningkatan Transportasi Laut Di Kepulauan Seribu Dalam Perspektif Sistem Pembangunan Wilayah Pesisir Dan Laut Secara Terpadu - Kurniawati, Fita (Warta Penelitian Perhubungan, 2010)
Kepulauan Seribu is a small-islands cluster's region. It has to be seen as an integrated region in whichsea transportation plmjs a major role in accelerating regional economtj and as a connector as well. Tirelimitation of transportation has its implimtion to the constraint of senrices and goods distnbutions.As a matter of fact, tlrere' s a tendene1; for the local peopl.e to prauide their own trnnsportntion in orderto fulfill tlreir needs. Meanwhile one of the main rol.e of the gonmrnient as a publlic seniant is toprovide mass transportntion for tlze citizen. As indicated biJ tire conditions above with tire purpose oftransportation impravenrent in order to develop integrated small islands cluster's regional therefore,this research is conducted using Integrated Cmstnl Zone Mnnagenrent (ICZM) as an approach. Tireresult of tire study slwwed that almost 90% respondents are not satisfied for tire transportationoperational and 50% respondents quite satisfied for the port facilities. In addition, biJ conducting LQanalysis Kepulauan Senbu identified !ms big potentinl from its fishing sector and from SWOT analysistlrere are sonre strategies identified wlziclz di"liideri into four aspects; transportntion SIJStem, law,regional and public.